Gender-role Perception and Employment Status in the Self-efficacy of Women - Rath, Sangeeta; Mishra, Aakankshya (European Journal of Sustainable Development, 2013)
The effect of gender-role perception and employment status on the self-efficacy of womenis examined. The study adopted a 2 (androgynous and sex-typed) X 2 (employed andunemployed) factorial design. One hundred and twenty women participated in the study.The sample consistsof 60 employed and 60 unemployed women. Both the groups ofemployed and unemployed women are categorized into androgynous and sex-typed on thebasis of the median split of their scores on the measure of androgyny. The respondents ofall the four groups are compared with respect to their level of perceived self-efficacy. Theresults indicate that androgynous women show better sense of efficacy compared to sex-typed women. The results further indicate that employed women have better sense of self-efficacy than unemployed women.